Synthesis of photoaddressable polymeric networks having azobenzene moieties and alkyl-chains-containing compounds - Orofino, Antonela Beatriz (2013)
We discuss the synthesis of new optically active polymeric networks containing azobenzene moieties and different alkyl-chaincontaining compounds. An epoxy resin based on diglycidyl ether of bisphenol A (DGEBA) was reacted with metaxylylenediamine (MXDA). An azo prepolymer (TAZ) was synthesized by reaction between Disperse Orange-3 and DGEBA. Reaction between palmitic acid (PA) and DGEBA was performed using triphenylphosphine as catalyst of the epoxy–acid reaction employing variable molar ratios of epoxy to carboxyl groups (r = 1, 2, 4). These precursors were called PA1, PA2 and PA4. Crosslinked epoxy-based azopolymers containing variable PA-based precursor content and constant chromophore concentration equal to 20 wt% TAZ were synthesized. Their reversible optical storage properties were studied and compared. It was found that the optical response is a direct consequence of the morphologies generated, and that crystallization of PA-based precursor can take place. When the PA-based precursor is not covalently bonded to the matrix, e.g. PA1, the remaining birefringence is high. PA4-modified materials present a completely different response, showing a behaviour that could be of great importance in the development of optical switchers. In this case, the organic tails remain dissolved in the matrix and unable to crystallize, giving a typical ‘on–off’ response.